When neoliberals become activists: social crisis threats motivate ingroup and outgroup prosociality among neoliberals - Stollberg, Janine; Koch, Franziska; Jonas, Eva (Frontiers in Psychology, 2025)
IntroductionPeople who support neoliberal beliefs (i.e., who believe in individual responsibility and meritocracy) are less motivated to collectively act against social inequality or help those in need. At the same time, economic and humanitarian crises put a spotlight on injustice and harm. They represent an existential threat to people and should thus motivate prosocial behavior in line with salient humanitarian values.MethodsWe conducted two experimental studies. Study 1 (N = 175) made an economic crisis salient. Study 2 (N = 205), conducted four weeks after the outbreak of the Ukrainian war, made the associated humanitarian crisis salient.ResultsWe found raising people's awareness of a social crisis (compared to a non-threatening control condition) increased prosociality and solidarity-based collective action, even when this conflicted with participants' neoliberal beliefs. In Study 1, a salient economic threat (compared to prosperity) buffered the negative effect of neoliberalism on prosociality and system change. In Study 2, the salient (vs. not salient) consequences of the Ukrainian war, increased solidarity with Ukrainian refugees, thereby overruling the negative effects of neoliberalism. Mediational analysis suggested that the threat effects on solidarity with Ukrainians were due to increased outgroup identification following threat. In both studies, the effects of neoliberalism were independent of related constructs, such as political conservatism or social dominance orientation.DiscussionThe results show that social crisis threats can make neoliberalists more flexible in applying their ideological beliefs. The findings are discussed in the context of group-based processes in response to threats.